2019
DOI: 10.1103/physrevx.9.021015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Formation of PbSe Honeycomb Superstructures by Dynamics Simulations

Abstract: Using a coarse-grained molecular dynamics model, we simulate the self-assembly of PbSe nanocrystals (NCs) adsorbed at a flat fluid-fluid interface. The model includes all key forces involved: NC-NC shortrange facet-specific attractive and repulsive interactions, entropic effects, and forces due to the NC adsorption at fluid-fluid interfaces. Realistic values are used for the input parameters regulating the various forces. The interface-adsorption parameters are estimated using a recently introduced sharpinterf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 117 publications
2
32
0
Order By: Relevance
“…Hanrath et al showed that large cubic PbSe NCs with an edge length of 25 nm do align a [111] axis perpendicular to the toluene-air interface, but there the NCs formed 3-D body-centered cubic superlattices 25 . This is also the orientation that PbSe NCs are required to have before silicene-type honeycomb superlattices can form 7,22 . We will show in the section below that the full adsorption geometry of the PbSe NCs studied here is determined by an interplay between the adsorption energy, mostly dictated by the NC size, and the degree of truncation of the NCs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Hanrath et al showed that large cubic PbSe NCs with an edge length of 25 nm do align a [111] axis perpendicular to the toluene-air interface, but there the NCs formed 3-D body-centered cubic superlattices 25 . This is also the orientation that PbSe NCs are required to have before silicene-type honeycomb superlattices can form 7,22 . We will show in the section below that the full adsorption geometry of the PbSe NCs studied here is determined by an interplay between the adsorption energy, mostly dictated by the NC size, and the degree of truncation of the NCs.…”
Section: Resultsmentioning
confidence: 93%
“…Which factors determine the amount of disorder on both atomic and NC length scales and how can we reduce this 10,[15][16][17][18][19][20][21] ? A recently introduced simulation model to predict the self-assembly of NCs at fluid-fluid interfaces provided fundamental insights that will help to answer these questions 22,23 .…”
mentioning
confidence: 99%
“…Further details on this model are reported in Supporting Information 6 and a recent publication. 53 In the simulations presented here, up to 10 4 NCs are initially randomly dispersed in a cubic box of side L aligned with a Cartesian coordinate system x , y , z and with periodic boundary conditions. The external force −d U 2D ( z c )/d z c is applied to each NC center of mass, with z c the z coordinate of the NC center of mass, to model the effect of the evaporating solvent, which compresses the NCs in a 2D plane.…”
Section: Resultsmentioning
confidence: 99%
“…The parameter u z is 10 –19 J, in line with predicted solvent–air adsorption potentials of NCs. 53 During the first 0.1 μs of simulation, the beads of different NCs interact with each other only by a soft repulsive pair potential, mimicking the effect of ligand molecules chemisorbed on the NC surface where r is the bead–bead center-of-mass distance, ϵ R is the magnitude of the repulsive potential, and σ R is the ligand length. After 0.1 μs, the attractive pair potentials between beads belonging to NCs’ {100} facets are (gradually) turned on, mimicking ligands detaching from {100} facets (thus allowing the facet–facet interaction).…”
Section: Resultsmentioning
confidence: 99%
“…Several different MD approaches have been used to study the formation of lead chalcogenide superstructures. , Recent work by Wang et al used MD simulations to study superlattice phase transitions for small 1D structures, focusing on the deformability of PbSe NCs during the phase transition and its impact on disorder. The force field used in that study considered only nonbonded interactions, namely, a short-ranged Lennard-Jones part and a long-ranged Coulombic part.…”
mentioning
confidence: 99%